Video Frames Reconstruction Based on Time-Frequency Analysis and Hermite Projection Method. (18th August 2010) - Stanković, Srdjan; Orović, Irena; Krylov, Andrey
Abstract : A method for temporal analysis and reconstruction of video sequences based on the time-frequency analysis and Hermite projection method is proposed. The S-method-based time-frequency distribution is used to characterize stationarity within the sequence. Namely, a sequence of DCT coefficients along the time axes is used to create a frequency-modulated signal. The reconstruction of nonstationary sequences is done using the Hermite expansion coefficients. Here, a small number of Hermite coefficients can be used, which may provide significant savings for some video-based applications. The results are illustrated with video examples.